Electrothermal treeing application for joul heating of oil shale; Известия вузов. Физика; Т. 57, № 12-3 - Martemyanov S. M. Sergey Mikhailovich; Lopatin V. V. Vladimir Vasilyevich; Bukharkin A. A. Andrey Andreevich; Koryashov I. A. Iliya Aleksandrovich (2014, 2014)
Заглавие с экрана